2008
DOI: 10.1111/j.1600-051x.2008.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health status and smoking among young adults

Abstract: Only 7% of the participants demonstrated signs of periodontitis and most young adults did not smoke; a dose-response association was revealed between present smoking habits and periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
22
0
3
Order By: Relevance
“…People in lower SEP tend to have poor oral hygiene, and smoke more tobacco (Gundala & Chava 2010). There is also evidence that tobacco smokers tend to have poorer oral hygiene than non‐tobacco smokers (Pejcic et al 2007, Vered et al 2008). These data, from the literature, provided the evidence‐based theory for the conceptual model, which has been proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…People in lower SEP tend to have poor oral hygiene, and smoke more tobacco (Gundala & Chava 2010). There is also evidence that tobacco smokers tend to have poorer oral hygiene than non‐tobacco smokers (Pejcic et al 2007, Vered et al 2008). These data, from the literature, provided the evidence‐based theory for the conceptual model, which has been proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Vered et al .,[20] evaluated the periodontal status and present smoking habits among a representative sample of young adult Israelis, and investigated possible associations and concluded that only 7% of the participants demonstrated signs of periodontitis and most young adults did not smoke.…”
Section: Introductionmentioning
confidence: 99%
“…López et al 6 found that nearly 25% of the adolescent participants in Chile were daily smokers. A study by Vered et al 21 found that 36% of the 7,056 Israeli army recruit participants were smokers, with 21% smoking more than 10 cigarettes per day. Rothlisberger et al 13 found that 32% of the 626 Swiss army recruit participants described themselves as smokers.…”
Section: Clinical Examinationmentioning
confidence: 99%